Exploring Halal Supply Chain Management in Islamic Boarding School: Insight from Pesantren Muhammadiyah - Zahra, Qiny Shonia Az; Mutmainah, Lu'liyatul; Andani, Listia; Friantoro, Dian (JURNAL AGROINDUSTRI HALAL, 2024)
Islamic boarding schools as traditional Islamic educational institutions have an important role in building a healthy and sustainable halal ecosystem. Islamic boarding schools must also ensure that the supply chain from upstream and downstream is in accordance with Halal Supply Chain Management (HSCM). Several HSCM applications start from supplier selection, production processes, storage, to distribution to consumers. The aim of this research is to analyze the application of HSCM and propose an HSCM model in Islamic boarding schools. This research includes qualitative research. Data was collected using interview, observation and documentation techniques and then analyzed using an inductive approach. This research was conducted at the Al-Furqon Muhammadiyah Islamic Boarding School, Tasikmalaya, taking 12 respondents. Respondents were selected based on their relationship with HSCM in Islamic boarding schools, from Islamic boarding school managers, teachers, kitchen managers, to students. This research shows that the implementation of halal supply chain management at the Al Furqon Muhammadiyah Islamic Boarding School, Tasikmalaya Regency is quite good with restrictions and education for proper and halal consumption. Providing nutritionists and halal food as well as a halal warehouse are needed to build a halal ecosystem in Islamic boarding schools. Providing halal certified raw materials also needs to be considered. Apart from that, funding through productive waqf can also be done to support the halal ecosystem in Islamic boarding schools.